The Thirteenth Sultan Azlan Shah Law Lecture 1998: Certainty And Justice: The Demands On The Law In A Changing Environment - Lord Nolan, The Right Honourable (Journal of Malaysian and Comparative Law, 1999)
Text of the Thirteenth Sultan Azlan Shah Law Lecture (organised by the Faculty of Law, University of Malaya and the British Council) delivered by the Rt Hon Lord Nolan, on 28 August 1998 in presence of DYMM, Sultan Azlan Shah, the Sultan of Perak.